A questão da superveniência do direito no Marxismo jurídico brasileiro - SOUZA, Nathalia Karollin Cunha Peixoto de (Universidade Federal do Pará, 2018)
Having found two general opposing poles of Brazilian legal Marxist theory, we sought to analyze which of these two positions had a greater consonance with the theory developed by Marx. In this respect, the two divergent groups of Brazilian thought diverged under one fundamental aspect: law's superposition or not over capitalism. If the greater divergence between the two groups is the matter of whether or not law is supervening, or, what amounts to the same, if the greatest divergence between them is the question of whether or not the legal form is specific, we can conclude as a consequence that the touchstone of legal Marxist analysis boils down to whether Marx's theoretical work goes either along the lines of assigning an instrumental revolutionary role to law or, on the contrary, if Marx had actually attributed a conservative role to Bourgeois order to the legal form. As a response to the problem, after the analysis of Marx's work, it was possible to conclude that law is a social form that arose pari passu to the birth of the universal circulation of goods; The universal circulation of commodities, in turn, only became possible with the capitalist mode of production; Therefore, law was only possible with the establishment of capitalism. In this sense, it becomes possible to deduce that law is a specificity of the bourgeois system. In this way, the thesis of law's non-superposition has been confirmed. Communist right is, given these conclusions, unthinkable. Finally, as representatives of these two groups of opposing views on the theme of Marxism and law in Brazil, we opted to analyze the work of Lyra Filho, as a representative of the position in defense of the thesis of the superposition of law, as well as opting to study, as representatives of the opposing group, the works of Naves, Mascaro and Kashiura Jr.